41st AIAA/ASME/SAE/ASEE Joint Propulsion Conference &Amp;amp; Exhibit 2005
DOI: 10.2514/6.2005-4277
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of the 11-By 11-Foot Transonic Wind Tunnel at the NASA Ames Research Center

Abstract: A series of calibration and flow survey tests were conducted in the 11-By 11-Foot Transonic Wind Tunnel following the modernization of the Unitary Plan Wind Tunnel at the NASA Ames Research Center. These tests included measurements of the static and total pressure which are required to develop the calibration tables used to compute the facility tunnel conditions and to correct the model airplane data for longitudinal buoyancy effects. Measurements of the total temperature, flow angle, and boundary layer charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Therefore, the test matrix of the ACSM will be defined for the validation test such that two highly accurate long static pipe calibrations of the test section can be used (i) to set the uncorrected Mach numbers for the angle of attack sweeps and (ii) to determine clear tunnel buoyancy (see Ref. [9] for more details). Figure 3b shows the location of the long static pipe when the test section was originally calibrated with slots on the test section side walls, the ceiling, and the floor in "open" configuration.…”
Section: B Mach Number Calibrationmentioning
confidence: 99%
“…Therefore, the test matrix of the ACSM will be defined for the validation test such that two highly accurate long static pipe calibrations of the test section can be used (i) to set the uncorrected Mach numbers for the angle of attack sweeps and (ii) to determine clear tunnel buoyancy (see Ref. [9] for more details). Figure 3b shows the location of the long static pipe when the test section was originally calibrated with slots on the test section side walls, the ceiling, and the floor in "open" configuration.…”
Section: B Mach Number Calibrationmentioning
confidence: 99%
“…The wind tunnel is driven by a 3-stage compressor turned by a 176 MW electric motor system. A general description of the facility can be found at http://windtunnels.arc.nasa.gov/, and the facility is additionally described by Amaya & Kmak 17 as well as Amaya & Boone 18 , from which the present description is taken. Readers seeking more detailed information are referred to the NASA Ames UPWT test planning guide 19 .…”
Section: A 27% Common Research Modelmentioning
confidence: 99%
“…As part of the CEV (now Orion) program, an experimental study 40,41 of the CEV geometry (shown in figure 21) was conducted at the Ames Unitary Plan Wind Tunnel (UPWT) 42 in the 11-foot Transonic Test Section and the 9X7 foot Supersonic Test Section. Test data were obtained for conditions at 0.3 ≤ M ∞ ≤ 2.5, 140…”
Section: Iif Orion Capsulementioning
confidence: 99%